ECG body surface mapping (BSM) in type 1 diabetic patients - Janíčková Žďárská, Denisa; Pelíšková, Pavlína; Charvát, Jiří; Slavíček, Jaroslav; Mlček, Mikuláš; Medová, Eva; Kittnar, Otomar (Physiological research, 2007)
Diabetes mellitus is a risk factor of cardiovascular diseases. ECG of patients with diabetes mellitus type 1 (DM 1) shows tachycardia (block of parasympathetic innervation) and abnormal repolarization (increased QT interval and QT dispersion (QTd)) indicating a risk of ventricular tachycardia and sudden death in young people with DM 1. The aim of the present report was to measure 145 parameters of the heart electric field in 22 patients (14 men, 8 women) with DM 1 without complications (mean age 32.8±11.4 years) and in 22 controls (11 men, 11 women, mean age 30.1±3.4 years). The duration of diabetes was 13.9±7.8 years. The parameters were registered by the diagnostic system Cardiag 112.2 and statistically evaluated by the Student and Mann-Whitney test. Tachycardia (86.3±2.7 beats.min-1), shortening of both QRS (79.9±1.6 ms) and QT (349.0±5.9 ms) and increased QT dispersion (115±36 ms) were observed in DM 1 when compared with the controls (75.0±2.1 beats. min.-1, QRS 89.9±2.7 ms, QT 374.0±4.4 ms, QTd 34.0±12.0 ms, p<0.01). The QTc was 415.2±4.1 ms in DM 1 and 401.4±6.6 ms in controls (NS). Other significant findings in DM 1 were: higher maximum of depolarization isopotential maps (DIPMmax) in the initial phase of QRS and less positive in the terminal phase, more negative minimum (DIPMmin) during QRS similarly as the minimum in depolarization isointegral maps (DIIMmin) and the minimum in isointegral map of the Q wave (Q-IIMmin), lower maximum in repolarization isopotential maps (RIPMmax) and less negative minimum (RIPMmin), more negative amplitude of Q wave (Q-IPMAM) and more pronounced spread of depolarization (activation time). Our results confirmed a decreased parasympathetic to sympathetic tone ratio (tachycardia, shortening of the activation time) and revealed different depolarization and repolarization patterns in DM 1. The differences in heart electric field parameters measured by the BSPM method in DM 1 and in the controls indicate the importance of ECG examination of diabetic patients type 1 in the prevention of cardiovascular diseases.
Keywords: elektrokardiografie; financování organizované; kardiovaskulární nemoci; Financing, Organized; diabetes mellitus; Diabetes Mellitus; Vectorcardiography; vektorkardiografie; Data Interpretation, Statistical; mapování potenciálů tělesného povrchu; Cardiovascular Diseases; inzulin; interpretace statistických dat; Insulin; Body Surface Potential Mapping; Electrocardiography